2021
DOI: 10.1111/1759-7714.14072
|View full text |Cite
|
Sign up to set email alerts
|

tRNA‐derived fragments: tRF‐Gly‐CCC‐046, tRF‐Tyr‐GTA‐010 and tRF‐Pro‐TGG‐001 as novel diagnostic biomarkers for breast cancer

Abstract: Background: tRNA-derived fragments (tRFs) have been found to play a regulatory role in the occurrence and development of many tumors. The aim of this study was to identify the expression of tRFs in breast cancer and their ability to serve as diagnostic markers for breast cancer. Methods: Total RNA was extracted from breast cancer and paracancerous tissues (n = 83), as well as from the sera of breast cancer patients (n = 214) and healthy donors (n = 113) using trizol reagents. Expression of tRFs was then detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 35 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…High-throughput RNA sequencing technology has facilitated the identification of novel non-coding small RNAs, including tsRNAs, as diagnostic biomarkers for cancers of the breast, colon, rectum, and stomach. [18][19][20][21][22] A previous study by our group found that tRF-5026a (tRF-18-79MP9P04) acts as a tumor suppressor in GC through the PTEN/PI3K/ AKT signaling pathway. 16 As a continuation of this work, the results of this study determined that tRF-18-79MP9P04 was an 18-nt segment derived from the 5' ends of tRNA-Val-AAC and tRNA-Val-CAC, belonging to the tRF-5 subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High-throughput RNA sequencing technology has facilitated the identification of novel non-coding small RNAs, including tsRNAs, as diagnostic biomarkers for cancers of the breast, colon, rectum, and stomach. [18][19][20][21][22] A previous study by our group found that tRF-5026a (tRF-18-79MP9P04) acts as a tumor suppressor in GC through the PTEN/PI3K/ AKT signaling pathway. 16 As a continuation of this work, the results of this study determined that tRF-18-79MP9P04 was an 18-nt segment derived from the 5' ends of tRNA-Val-AAC and tRNA-Val-CAC, belonging to the tRF-5 subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma tRFs present promising novel diagnostic biomarkers for breast cancer 24 as well as other malignancies. [6][7][8] A study conducted by Zhang et al 22 found that tRF-Gly-CCC-046, tRF-Tyr-GTA-010, and tRF-Pro-TGG-001 combined with some traditional biomarkers could be used to effectively monitor the progression of breast cancer. At present, diagnosis of GC is mainly based on endoscopic and histopathological examinations of lesions and a differential diagnosis is usually required to distinguish primary GC from other diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, 45 studies that did not meet the inclusion criteria were excluded, and the full texts of the remaining 56 studies were reviewed in detail. Finally, 13 studies (involving 7 prognosis, 7 diagnosis, and 3 clinicopathological features) were included in the meta-analysis (13,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The detailed literature selection process is illustrated inFigure 1 .…”
Section: Literature Information and Study Characteristicsmentioning
confidence: 99%
“…tRF profiling studies in breast cancer identified several new biomarkers for breast cancer diagnosis and/or progression. By profiling 83 breast cancer tissues and 214 serum samples from breast cancer patients, Zhang et al (2021) identified tRF‐Gly‐CCC‐046, tRF‐Tyr‐GTA‐010 and tRF‐Pro‐TGG‐001downregulated in tumor tissues that could also serve as circulating markers. A similar study (Wang et al 2021) carried out by analyzing a cohort of 120 breast cancer samples and 112 normal controls, identified a signature of 15 tRFs upregulated in breast cancer.…”
Section: Trfs In Solid Cancersmentioning
confidence: 99%